Anti-MOG Antibody-Associated Unilateral Cortical Encephalitis with Bilateral Meningeal Involvement: A Case Report - Bo Ren; Shiying Li; Bin Liu; Jinxia Zhang; Yaqing Feng (Brain Sciences, 2023)
A 27-year-old Han Chinese woman presented with fever, headache, lethargy, and difficulty in expression. Magnetic resonance imaging (MRI) detected extensive hyperintensity of the left-sided frontoparietal, temporal, occipital, and insular cortices via fluid-attenuated inversion recovery (FLAIR) imaging. Post-contrast MRI revealed linear enhancement in the frontoparietal, temporal, and occipital sulci bilaterally. The detection of anti-myelin oligodendrocyte glycoprotein (MOG) was positive in the cerebrospinal fluid (CSF) and serum. The patient was diagnosed with anti-MOG antibody-associated unilateral cortical encephalitis with bilateral meningeal involvement. The patient received low doses of intravenous dexamethasone followed by oral prednisone, which was tapered until withdrawal. The treatment significantly improved the patient’s symptoms. A one-month follow-up showed that the patient gradually resumed her normal lifestyle. No further relapse was recorded after a one-year follow-up. MRI performed almost a year after the initial symptom onset showed that the FLAIR signal had decreased in the left insular lobe, and the abnormal cortical signal of the FLAIR in the original left frontotemporal occipital lobe had disappeared. Thus, we report a rare case of anti-MOG antibody encephalitis (unilateral cortical encephalitis with bilateral meningeal involvement) in an adult patient. This study provides a reference for the clinical diagnosis and treatment of MOG antibody-associated unilateral cortical encephalitis.